Analysis of the features of affective and neurotic psychopathological symptoms in cosmetological patients - Юдін, Михайло Анатолійович (ScienceRise: Medical Science, 2016)
The significant prevalence of psychic pathology among patients of the medical sphere, including medical cosmetology puts a question about organization of medical-psychological help for this category of patients/clients. Aim of research – to reveal the features of the structure of affective-neurotic psychopathological symptoms in cosmetological patients. Contingent and methods of research. The testing included 286 women, who asked for cosmetological help. The interrogated were divided in three groups on the base of self-relation criterion: 1 group included persons with disharmonious type with tendency to the understated self-appraisal (G1, n=108), 2 group – with harmonious type (G2, n=96) and 3 group – with disharmonious type with inclination to the overstated self-appraisal (G3, n=82). Determination of the intensity of psychopathological symptoms was carried out by the SCL-90-R method. Results. The main manifestations of affective-neurotic symptoms in women with disharmonious type of self-relation with inclination to understated self-appraisal were somatization on astheno-neurotic type, the expressed anxiety component (worry, strain, fear, waiting for troubles, excessive bother), indecisiveness, need to verify the own actions, intrusive ideas, lack of forces, hypothymia, self-accusation, feeling of necessity of excessive efforts for own activity, discomfort in populous places; in patients with inclination to overstated self-appraisal – somatization with illogical and hysteroid manifestations, strain, nervousness, excessive bother, intrusive ideas, feeling of loneliness, depression. In women with harmonious self-relation somatization was manifested mainly by cephalalgias, strain, less nervousness, intrusive ideas, the necessity to verify the own actions and hypothymia. The structure of psychopathological symptoms in cosmetological patients reflected the meaningful features and directionality of psychic reaction to stress. Conclusions. The women, who ask for the medical care, form the group, heterogenic by psychological characteristics that must be taken into account at giving medical and psychological help. The patients with disharmonious type of self-relation, especially the ones with inclination to understated self-appraisal, form the risk group as to the psychic health and need medical-psychological help